2001
DOI: 10.1246/cl.2001.108
|View full text |Cite
|
Sign up to set email alerts
|

Spiropyran as a Regulator of DNA Hybridization with Reversed Switching Mode to That of Azobenzene

Abstract: The nitrospirobenzopyran, tethered at the 5′-end of the homothymidine, was thermally isomerized to colored merocyanine, which was converted reversibly to colorless spiropyran by visible light irradiation (λ > 490 nm). Concurrently with the spiropyran→merocyanine isomerization, melting temperature of the duplex with its complementary oligonucleotide was changed from 18.0 °C to 21.6 °C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
34
0
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 15 publications
0
34
0
4
Order By: Relevance
“…[242][243][244] Bisher hat aber die Labilität der HTIs gegenüber typischen Bedingungen für die Peptidfestphasensynthese ihren Einsatz als konformative Schalter für Peptide stark beeinträchtigt. [256] Die Konjugation eines Nitrospirobenzopyrans an ein Oligonukleotid -entweder über einen Linker an das 5'-Ende [257] oder intern an ein 2'-OH [258] (siehe 28 in Abbildung 14) -resultierte in einem Verlust der Photoaktivität für das Schalten der SP-in die MC-Form. Zwar ist ihr photochemisches Verhalten schwerer vorherzusagen und auch mehr durch die Umgebung beeinflussbar als bei Azobenzolen.…”
Section: Andere Photoschalterunclassified
See 1 more Smart Citation
“…[242][243][244] Bisher hat aber die Labilität der HTIs gegenüber typischen Bedingungen für die Peptidfestphasensynthese ihren Einsatz als konformative Schalter für Peptide stark beeinträchtigt. [256] Die Konjugation eines Nitrospirobenzopyrans an ein Oligonukleotid -entweder über einen Linker an das 5'-Ende [257] oder intern an ein 2'-OH [258] (siehe 28 in Abbildung 14) -resultierte in einem Verlust der Photoaktivität für das Schalten der SP-in die MC-Form. Zwar ist ihr photochemisches Verhalten schwerer vorherzusagen und auch mehr durch die Umgebung beeinflussbar als bei Azobenzolen.…”
Section: Andere Photoschalterunclassified
“…Zwar ist ihr photochemisches Verhalten schwerer vorherzusagen und auch mehr durch die Umgebung beeinflussbar als bei Azobenzolen. Weiterhin wird die Hydrolysestabilität von Spiropyranen als nachteilig für biologische Anwendungen angesehen, da für Spiropyrane ein schneller Abbau bei 60 8C in wässrigem Puffer [260] und unter wässrig-basischen Bedingungen [257,258] festgestellt wurde. Konjugation an ein Biomolekül erfolgt meistens über das N-Atom der Indolhälfte eines Spiropyrans, allerdings kçnnen auch andere Stellen des Moleküls modifiziert werden, was eine Orientierungskontrolle des Schalters im Biokonjugat zulässt.…”
Section: Andere Photoschalterunclassified
“…As expected, ground-state interactions between the noncovalently bound molecular switch and the DNA bases were detected in the case of the merocyanine form by CD spectroscopy, but not in the case of the spiropyran form. Attempts to attach spiropyrans covalently to DNA are rare [2627] and include our recent approaches to incorporate synthetically the spiropyran chromophore [28], by either DNA building block 1 [29] or by DNA base modifications 2 and 3 [2930], into oligonucleotides (Scheme 1). Although the spiropyran DNA building blocks 1 and 2 exhibit promising photochromic properties as nucleosides, it is not worth pursuing this synthetic direction further for the following reasons [30]: (i) It is reported that spiropyrans decompose in aqueous buffer solutions [31], and (according to our experience) the DNA environment does not efficiently prevent this decomposition.…”
Section: Introductionmentioning
confidence: 99%
“…15 Spiropyrans have recently been shown to offer much promise for biological and biotechnological applications, including the photoswitching of protein activity, 16,17 optical control of ion penetration through biological membranes 18 and regulation of DNA hybridization. 19 The generic scenario of photochromic transformation of spiropyran molecules involves C-O bond cleavage (see the inset in Fig. 1) and relaxation from a transient state to a metastable merocyanine-form state.…”
Section: Introductionmentioning
confidence: 99%